Synthesis and application of Zn/Ce bimetallic oxides for the decontamination of arsenite (As-III) ions from aqueous solutions - Banerjee S.; Sharma Y.C. (My University, 2025)
Arsenic contamination has threatened water safety due to its high toxicity and carcinogenicity. Therefore, it is urgent and significant to develop simple and effective approach for dearsenification of drinking water. In present study, Zn/Ce bimetallic oxide particles of various atomic ratios were synthesized by sol-gel process and were applied for adsorption of arsenite from aqueous solutions. The Zn/Ce bimetallic oxide of atomic ratio Zn0.2:Ce0.05 shows better adsorption proficiency in comparison to their monometallic counterparts as well as synthesized bimetal oxides of other atomic ratios. Sorption behavior of arsenite on Zn/Ce bimetal oxide was investigated through batch experiments and optimum conditions were found to be pH = 7.5, adsorbent dose = 0.36 g/L, and contact time = 30 min. The arsenite adsorption data was explained by Langmuir isotherm model and maximum adsorption capacity found to reaching 88.49 mg/g at 318 K. Adsorption mechanism was interpreted using FTIR and XPS data, the former suggesting formation of bond between As(III)–Zn/Ce oxide nanoparticles while, latter reveals presence of both As(III) and As(V) peak which further infer that some fraction of As(III) may be get oxidized to As(V) by O2 based on Ce3+ as electron mediation agent between As(III) and O2. © 2018 Elsevier Ltd